2001
DOI: 10.1002/jcp.1079
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type1 receptor regulation and differential trophic effects on rat cardiac myofibroblasts after acute myocardial infarction

Abstract: Fibroblast growth in the scar and surviving tissue is a key element of the remodeling post myocardial infarction. The regulation of fibroblast growth after acute myocardial infarction remains to be determined. Recently, Angiotensin II has been demonstrated to be a mitogen for neonatal cardiac fibroblasts. In this study adult rat cardiac fibroblasts were isolated from different regions of the infarcted rat heart and Angiotensin II effects examined. Adult Wistar-rats were sham operated or left coronary artery li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…In a MI model, a previous study (32) has shown that the in vivo CF phenotype is stable and can be studied in culture up to passage 4. The methodologies presented here are consistent with previous reports examining protein expression and signaling by CFs isolated from rats after MI and studied in culture (3,15,16,30). However, unlike these studies, which examined CFs at early time points (Յ4 wk) post-MI, we examined the long-term effects of MI on AC function and collagen production to understand the role of AC in CF function in the late phase of remodeling.…”
Section: Discussionsupporting
confidence: 72%
“…In a MI model, a previous study (32) has shown that the in vivo CF phenotype is stable and can be studied in culture up to passage 4. The methodologies presented here are consistent with previous reports examining protein expression and signaling by CFs isolated from rats after MI and studied in culture (3,15,16,30). However, unlike these studies, which examined CFs at early time points (Յ4 wk) post-MI, we examined the long-term effects of MI on AC function and collagen production to understand the role of AC in CF function in the late phase of remodeling.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, TGF-β1-induced IL-6 expression participated in trans-differentiation of fibroblasts to myofibroblasts [16]. In the myocardium, activated myofibroblasts are the main source of extracellular matrix proteins such as collagen I/III and fibronectin [17], [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac remodelling is associated with increased cardiac mass, the accumulation of interstitial collagen and decreased cardiac contractility 1,2 . During the process of cardiac remodelling, cardiac fibroblasts (CF), most of the non‐myocyte cells in the heart, undergo proliferation, differentiation and produce more extracellular matrix (ECM) proteins 3,4 . A variety of extracellular stimuli, such as mechanical stretch and some cytokines, activate cardiac fibroblasts, which are the source of most of the cardiac ECM and many cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 During the process of cardiac remodelling, cardiac fibroblasts (CF), most of the non-myocyte cells in the heart, undergo proliferation, differentiation and produce more extracellular matrix (ECM) proteins. 3,4 A variety of extracellular stimuli, such as mechanical stretch and some cytokines, activate cardiac fibroblasts, which are the source of most of the cardiac ECM and many cytokines. Cardiac fibroblasts are able to secrete transforming growth factor (TGF)-b1, endothelin (ET)-1, nitric oxide (NO), platelet-derived growth factor (PDGF)-A and so on.…”
Section: Introductionmentioning
confidence: 99%